ECO-LOKAL INQUIRY (ECO-LI): INTEGRATING GLOBAL ENVIRONMENTAL SUSTAINABILITY WITH TENGGER INDIGENOUS ECOLOGICAL KNOWLEDGE - Larasati, Diyas Age; Hanafi, Nurfirdawati Binti Muhamad (Jurnal Ilmiah Ilmu Terapan Universitas Jambi, 2026)
Environmental sustainability education in elementary schools is often delivered through global and abstract perspectives that are weakly connected to students’ local ecological and cultural contexts. This study aims to develop the Eco-Lokal Inquiry (ECO-LI) model, a culturally grounded inquiry-based learning framework that integrates Global Environmental Sustainability (GES) principles with Tengger Traditional Ecological Knowledge (TEK) to strengthen contextual and meaningful environmental learning. This study employed an integrative literature review design by systematically analyzing peer-reviewed journal articles, scholarly books, and international policy documents published between 2014 and 2024. Data were collected from Scopus, Web of Science, ERIC, and Google Scholar using explicit inclusion and exclusion criteria. An analytical instrument grid was used to extract key themes, which were then examined through thematic synthesis, comparative epistemological analysis, and conceptual model construction. The results of the analysis produced the ECO-LI model, which consists of five inquiry phases: contextual problem orientation, local ecological exploration, dialogic inquiry between indigenous knowledge and science, glocal reflection, and community-based environmental action. The findings reveal a strong conceptual alignment between GES dimensions—ecological integrity, social sustainability, and sustainability literacy—and Tengger ecological practices such as sacred forest protection, ritual-based conservation, and communal stewardship. This study demonstrates that inquiry-based learning can function as a dialogic space that bridges scientific sustainability frameworks and indigenous ecological worldviews without subordinating either knowledge system. The novelty of this research lies in its glocal inquiry framework, which positions TEK and science as complementary epistemologies within sustainability education.